Analysis of Locutionary, Illocutionary and Perlocutionary Speech Acts in Indomie Ads on Television - Nurul Khabibah; Intan Sari Ramdhani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Pragmatics is the science of linguistics which can analyze spoken words and derive their meaning. The development of pragmatics is driven by the awareness of linguists to explore pragmatics. Because humans cannot be separated from their daily communicative activities, the use of utterances in everyday life can be unlimited as speech acts, including locutionary acts, illocutionary acts, and perlocutionary acts. The type of research method in this article is qualitative with document type. Qualitative research is a type of research whose results are not based on statistics or other calculations. The purpose of this study is to find out what is meant by locutionary, illocutionary and perlocutionary as well as giving examples of the three.